RYE CHROMATIN INTROGRESSION IN THE BREAD WHEAT GENOME: CYTOGENETIC ASPECTS - O. G. Silkova; D. B. Loginova; Yu. N. Ivanova (Kabanenko); E. B. Bondarevich; L. A. Solovei; T. I. Shtyk; N. I. Dubovets (Вавиловский журнал генетики и селекции, 2015)
Alien chromatin introgression into the genome of common wheat Triticum aestivum L. is the most efficient way to enrich the gene pool of this crop. To improve the breeding value of wheat accessions, rye Secale cereale L is used as a donor of characters. Transfer of rye genetic material has certain specific features. The combination of the two cereal genomes in a single nucleus results in imbalance in all genetic systems. Fertility restoration in amphihaploids is the first step in the formation of introgression accessions. It is followed by the hybrid genome reorganization, which leads to cytological and genetic stability in the diploid progeny. In this paper, we present and analyze results that were obtained in the study of the two steps of wheat-rye hybrid genome reorganization: (1) breaching of F1 hybrid sterility (cytogenetic mechanisms of unreduced gamete formation) and (2) reorganization of wheat subgenomes during the introgression of single rye chromosomes.